2024
DOI: 10.3390/agriengineering6010048
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Comparison of CNN Models for Bean Phenology Classification Using Transfer Learning Techniques

Teodoro Ibarra-Pérez,
Ramón Jaramillo-Martínez,
Hans C. Correa-Aguado
et al.

Abstract: The early and precise identification of the different phenological stages of the bean (Phaseolus vulgaris L.) allows for the determination of critical and timely moments for the implementation of certain agricultural activities that contribute in a significant manner to the output and quality of the harvest, as well as the necessary actions to prevent and control possible damage caused by plagues and diseases. Overall, the standard procedure for phenological identification is conducted by the farmer. This can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In this architecture, there are blocks with convolutional layers in sequence and a separate parallel identity layer [43], which can result in a more precise extraction of color or texture features from plant leaf images [44]. In the ResNet-50 used, the technique of transfer learning, combined with pre-training on large datasets, was applied, which conferred an essential generalization capacity for classifying different nitrogen concentrations in strawberry leaves [45]. In addition, the application of residuals to the convolutions, a differential of ResNet-50, allows the network to learn residual differences in the image features, optimizing the model's training.…”
Section: Analysis Of the Modelsmentioning
confidence: 99%
“…In this architecture, there are blocks with convolutional layers in sequence and a separate parallel identity layer [43], which can result in a more precise extraction of color or texture features from plant leaf images [44]. In the ResNet-50 used, the technique of transfer learning, combined with pre-training on large datasets, was applied, which conferred an essential generalization capacity for classifying different nitrogen concentrations in strawberry leaves [45]. In addition, the application of residuals to the convolutions, a differential of ResNet-50, allows the network to learn residual differences in the image features, optimizing the model's training.…”
Section: Analysis Of the Modelsmentioning
confidence: 99%
“…In this study, the results showed good performance in all classes, with values ranging between 98.51 and 100%. Ibarra-Pérez et al [28] proposed a transfer learning approach to identify different phenological stages of beams using the CNN models AlexNet, VGG19, SqueezeNet, and GoogleNet. They used validation metrics like accuracy, precision, sensitivity, specificity, and F1-score to obtain the best results with the GoogleNet architecture, reporting the highest value of 98.73% for specificity.…”
Section: Introductionmentioning
confidence: 99%